OPTIMASI PARAMETER PROSES 3D PRINTING TERHADAP KUAT TARIK FILAMENT PETG MENGGUNAKAN METODE TAGUCHI - Silsa Zakaria; Rizky Stighfarrinata; Amalia Ma'rifatul Maghfiroh (JUSTI (Jurnal Sistem dan Teknik Industri), 2022)
3D Printing is the process of making products from a digital design into three-dimensional shapes that can be seen and can be held, and have volume. Where 3D Printer is a technology that has a bright future, even the technology is still growing and supporting humans for technological advancement. 3D Printer Type FDM (Fused Deposition Modelling) is very often used because it is easy to print three-dimensional objects at low cost and also filament material that has been widely available. By using the Taguchi method to find out the optimal process parameters, where finding the larger value is better in the results of the tensile test plot means and S/N ratio using analysis software and manual calculations. Using the SOVOL SV06 brand 3D Printer machine and SUNLU brand PETG filaments, it was found that the Print Speed factor or parameter greatly affects the tensile test strength according to ASTM D638 Type IV standards. Where after tensile tests and data processing both manually and with the help of software, the S/N ratio value was found with a sequence of parameters, namely Print Speed (50 mm/s), Layer Height (0.24 mm), Print Temperature (250 Â°C) and Infill Density (50%).